Taxes and the efficiency costs of capital distortions - Alfons J. Weichenrieder; Tina Klautke (Center for Economic Studies and ifo Institute (CESifo), 2008)
Tax neutrality towards alternative financing instruments for corporate investment is a ubiquitous demand in the political debate. At the same time, the literature is surprisingly silent about the magnitude of possible efficiency costs of a departure from tax neutrality. Against this background, the present paper discusses the theory of capital structure and provides backof-the-envelope calculations of the possible efficiency cost of a tax distortion of the debtequity decision.
Keywords: H25; G32; 330; Debt-equity choice; capital structure; excess burden of taxation; Steuerbelastung; Excess Burden; Kapitalstruktur; Wirtschaftliche Effizienz; Wohlfahrtseffekt; Theorie